Aligning Management Research in Asia-Pacific Region: an Indonesian Perspectives - Irawanto, Dodi Wirawan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
This notes discuss fundamental issues regarding future research on management research in Asia-Pacific, from Indonesian scholars point of view. In order to meaningfully introduce these issues, it begin with an overview of management research in Asia-Pacific – specifically research published in this journal, that briefly covering some of the similarities and differences between Asian and Western management approaches. The focus of this essay rely on the identification of fundamental issues describes in the introduction section that captured relationships between management concepts being studied. This essay end with further argue that for such an approach to be viable, fundamental issue in the philosophy issue underlying the importance of the research as well as the trend in using sophisticated statistical tools that heavily questioning the possible implication of the research in the practical arena.